Penentuan Daya Tampung Sungai Mayang Terhadap Beban Pencemaran Menggunakan Persamaan Streeter-Phelps - Sri Wahyuningsih; Elida Novita; Kiki Paradiba (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
The Mayang River in Jember Regency has a length of approximately 145.50 km which is the longest river and can irrigate an area of 5,860 hectares. The use of the Mayang River by the community can produce waste, both domestic waste, agricultural waste, and livestock waste. Waste that enters directly into river bodies can cause a decrease in river water quality and can create a pollution load. Therefore, the measurement of the load capacity of the Mayang River was conducted. Mayang River water samples were taken using the grab sampling method, while the river's capacity was determined using the Streeter Phelps method. The results showed that the average value of the Mayang River pollution load was 219,483 kg/day. Some of the parameters used to determine the carrying capacity of the river are the daily deoxygenation rate of 0.137 mg/L and the dailyy reaeration rate of 1.097 mg/L. It has a critical point (tc) of 0.186, a critical distance (Xc) of 4.753 km, and a critical deficit (Dc) of 0.281 mg/L. Based on these parameters, it is concluded that the Mayang River can accommodate a pollution load of 1.5 kg/day and can carry out proper purification. Keywords : grab sampling method, Streeter Phelps, the deoxygenation rate, the reaeration rate